The Gower handbook of management - Lock, Dennis (Gower, 1998)
A practical guide to best practice in management. By covering a broad range of subjects, the book aims to replicate a forum in which managers can meet experts from a range of professional disciplines. This edition features 65 expert contributors and 20 chapters on subjects new to this edition.